Treatment Of The Elderly In Ruskin Bond’s Short Stories (Journal of Pharmaceutical Negative Results, 2023)
It is a worldwide phenomenon that the older population has increased tremendously over the years as the life expectancy of individuals has improved as a result of great strides in health care. This has resulted in concerns and apprehensions about shifts in family values, relationships between the family members and financial adjustments. The younger generation is seen to be moving away from the traditional joint family due to several reasons, chiefly due to better educational and career opportunities. Although this has led to economic stability, it has several downsides too. The elderly, who are in need of emotional, financial and community support have been relegated to the side-lines, often neglected, and deprived of the warmth of human connection. “As long as a man has ability to earn and save, so long are all his dependants attached to him. But when he becomes old and infirm, even his family does not care to even speak a word with him.” - Adi Shankaracharya The celebrated author Ruskin Bond has addressed several social issues in his short stories such as loneliness in old age and the mental fragility of the aged. He is deeply conscious of the myriad problems that are at the core of the alienation felt by the people of an advanced age and his stories give the readers an empathetic rendering of the twilight years of their lives. In The Kitemaker, The Prospect of Flowers, The Garlands on His Brow and The Cherry Tree, Ruskin Bond has painted a vivid picture of the conditions in which older people find themselves and jolt the readers into realigning their values so that the elders can be find peace and contentment toward the end of their lives.